ChemInform Abstract: Chain Walking as a Strategy for Carbon—Carbon Bond Formation at Unreactive Sites in Organic Synthesis: Catalytic Cycloisomerization of Various 1, n‐Dienes. Issue 25 (June 2016) - Hamasaki, Taro; Aoyama, Yuka; Kawasaki, Junichi; Kakiuchi, Fumitoshi; Kochi, Takuya
Abstract: 20 examples